When research meets NGOs: The GVC-UCODEP project in the Bắc Giang Province and Cầu River (Northern Vietnam) and its feedback on national monitoring programs. Issue 101 (November 2019) - Giuliani, Silvia; Romanelli, Margherita; Piazza, Rossano; Vecchiato, Marco; Pizzini, Sarah; Tranchida, Giorgio; D'Agostino, Fabio; Romano, Stefania; Bellucci, Luca Giorgio
Graphical abstract: An example of how scientific and NGOs' worlds unite for the common purpose of people's wellbeing. Highlights: Fast-developing countries face the challenge of ensuring a sustainable development. Research and NGOs collaborated for the purpose of safe development in North Vietnam. The degree of POPs contamination was determined and national law limits verified. A series of suggestions were provided to better address specific pollution issues. The presented approach can be transferred to other developing countries. Abstract: The International Cooperation GVC-UCODEP project "Promotion of environmental protection in the Việt Yên, Yên Dũng and Hiệp Hòa districts in the Bắc Giang Province, Vietnam" aimed at the restoration and preservation of natural resources together with the improvement of life conditions of the local population. It focused on the management of pollutant factors and ecological resources of the Bắc Giang Province. An important part of the project was devoted to the implementation of an institutional frame for monitoring the status of the environment, and within this frame a scientific survey was promoted in order to assess the degree of contamination from persistent organic pollutants in soils and sediments of selected areas of the Bắc Giang Province and the bordering Cầu River. The toxicological significance of measured concentrations, and the relative importance of pollutant sources were also investigated. At the same time, enforced Vietnamese regulations were studied to check their effectiveness in protecting the population and the environment. Results of this combined work provided a series of suggestions to central and local authorities in order to ensure people's health and a better monitoring of local natural resources. It is our hope that the described approach and methodology could inspire similar synergies between research and non-governmental institutions in other developing countries.